3-Dimensional personalized planning for transcatheter pulmonary valve implantation in a dysfunctional right ventricular outflow tract. (15th June 2020) - Pluchinotta, Francesca R.; Sturla, Francesco; Caimi, Alessandro; Giugno, Luca; Chessa, Massimo; Giamberti, Alessandro; Votta, Emiliano; Redaelli, Alberto; Carminati, Mario
Abstract: Background: Identification of adequate landing zone for transcatheter pulmonary valve implantation (TPVI) is crucial to successfully treat an aneurysmatic native right ventricle outflow tract (RVOT); three-dimensional (3D) patient-tailored digital and physical printed models are available but their actual strengths and weaknesses still not well documented. The aim of the study was to tackle TPVI planning in the dysfunctional and borderline RVOT exploiting both digital and physical printed 3D patient-specific models. Methods: Electrocardiographically gated computed tomography (CT) angiography was segmented and anatomical RVOT geometrical changes dynamically tracked throughout the cardiac cycle using in-house processing. A compliant 3D-printed model was manufactured from the diastolic rest phase to test in vitro the catheter-based procedure feasibility; results were compared against CT-derived in vivo measurements and the actual catheterization outcome. Results: CT-gated analysis successfully quantified in vivo RVOT dynamic changes corroborating the feasibility of non-conventional pulmonary jailing percutaneous intervention. Clinicians used the 3D-printed model to test the steps of the jailing procedure; yet, the deformable 3D model printed at diastole underestimated the final implant dimensions obtained during cardiac catheterization by the same operators. Conclusions: Multidisciplinary synergy between CT-gated analysis and pre-procedural tests on 3D-printed phantoms can help the interventional team to tackle complex TPVI procedures. To fully exploit 3D-printed models, adequate selection of the still frame to print and tuning of printing material properties is crucial and can be aided by 3D dynamic virtual models. Graphical abstract: 3D personalized TPVI planning: dynamic CT-gated tracking of anatomical changes and pre-procedural tests on a 3D-printed phantom Unlabelled Image Highlights: CT-gated analysis can tackle TPVI feasibility in a borderline RVOT anatomy. 3D patient-tailored digital technologies can improve TPVI planning. Still frame to print and tuning of 3D-printing material properties is crucial. Training on 3D-printed phantoms can promote safe interventional skills acquisition.